A study on oxidative degradation of polyacrylamide in wastewater with UV/FENTON/C4H4O62−. Issue 1 (2nd January 2016) - Cao, Chun-Yan; Zhao, Yong-Hua; Zhou, Yan-Jun
ABSTRACT: The degradation of polyacrylamide (PAM) in simulate wastewater was studied in UV/Fenton/C4 H4 O6 2− system. The factors such as molecular ratio of H2 O2 /Fe 2+ /C4 H4 O6 2−, pH, and the dosage of Fenton reagent that could affect the PAM degradation in the UV/Fenton/C4 H4 O6 2− system were investigated. The experimental results showed that adding C4 H4 O6 2− to UV/Fenton system could form photosensitive ferrous complexes, which led to higher degradation efficiency of PAM. The degradation rate of PAM could be up to 95.2% under the following conditions: the concentration of H2 O2, Fe 2+, and C4 H4 O6 2− were 22.5, 2.25, and 2.25 mmol/L, respectively (i.e., molecular ratio of H2 O2 /Fe 2+ /C4 H4 O6 2− was 10:1:1), the pH value was 3.0.